Opportunity constraints and social inequalities in exercise participation: a lagged analysis using CFPS 2018–2022 - Xiwen Zhang; Wangjie Li (Frontiers in Public Health, 2026)
Background Insufficient physical activity is socially patterned, but education, residence, work, health, and internet access are often modeled as separate covariates rather than as cumulative conditions that enable or restrict exercise. Methods We analyzed individual-level longitudinal data from the China Family Panel Studies (CFPS) in 2018, 2020, and 2022. Two lagged person-period intervals were constructed: 2018–2020 and 2020–2022. The exposure was a standardized opportunity-constraint score ranging from 0 to 9, based on nine binary indicators across resource conditions, time conditions, health feasibility, and information access. The outcome was weekly exercise participation in the subsequent wave. Lagged logistic models adjusted for prior exercise participation, age, sex, marital status, period fixed effects, and province fixed effects; standard errors were clustered at the individual level. Results The analytic sample included 32,306 person-period observations from 19,956 respondents. Subsequent weekly exercise participation was 43.94% in the low-constraint group, 27.65% in the moderate-constraint group, and 19.24% in the high-constraint group. In adjusted models, moderate and high constraints were associated with lower odds of subsequent participation than low constraints (OR = 0.555, 95% CI: 0.524–0.588; OR = 0.369, 95% CI: 0.340–0.401, respectively; both p < 0.001). The continuous-score model showed a similar inverse association (OR = 0.764, 95% CI: 0.750–0.779, p < 0.001). Resource-, time-, and information-access constraints were inversely associated with the outcome, whereas health-feasibility constraints were not independently associated after mutual adjustment. In an individual fixed-effects logit sensitivity model, the continuous score was not associated with subsequent participation (OR = 0.996, 95% CI: 0.927–1.070, p = 0.908). Conclusion Multidimensional opportunity constraints were associated with a clear population-level gradient in subsequent weekly exercise participation. The null fixed-effects result indicates that this gradient should be interpreted as a between-person inequality rather than evidence of a short-term within-person causal association.